The Interplay of Brand Gestalt, Word-of-mouth and Revisit Intention in the F&B Sector - Langitan, Jentelino Silvester; Rondo, Elannemay; Mandagi, Deske W. (Jurnal Informatika Ekonomi Bisnis, 2024)
This research examines the influence of brand gestalt variables, especially the four dimensions, story, sensescape, servicescape, stakeholders, on word-of-mouth marketing and the revisit intention. This research has eight hypotheses with a sample size of 175 obtained from the distribution of questionnaires carried out in October and November 2023. The data obtained was analyzed using Structural Equation Modeling (SEM) assisted by the SmartPLS statistical program. The results obtained show that the brand gestalt dimensions that influence word of mouth marketing and interest in revisiting are only two dimensions, namely Stakeholder for word-of-mouth marketing and Story for interest in returning to visit. Additionally, the study found that the remaining six hypotheses did not yield significant influences. The results of this research can be a reference for the food and beverage sector so that it can improve the quality of its business by utilizing the results obtained.